2023
DOI: 10.3390/lubricants11070292
|View full text |Cite
|
Sign up to set email alerts
|

Current Knowledge on Friction, Lubrication, and Wear of Ethanol-Fuelled Engines—A Review

Abstract: The urgent need for drastic reduction in emissions due to global warming demands a radical energy transition in transportation. The role of biofuels is fundamental to bridging the current situation towards a clean and sustainable future. In passenger cars, the use of ethanol fuel reduces gas emissions (CO2 and other harmful gases), but can bring tribological challenges to the engine. This review addresses the current state-of-the-art on the effects of ethanol fuel on friction, lubrication, and wear in car engi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 60 publications
(130 reference statements)
0
4
0
Order By: Relevance
“…At the same time, ethanol has some tribological issues connected with engine oil dilution and corrosion [21] due to the inherent oxygen and moisture. Research [22] confirms that ethanol generally increases wear while having a minimal impact on the aging performance of lubricant oil [23]. Therefore, it could be concluded that conventional fuel modification by adding alternative fuels results in dilution and degradation of engine oil, which affect thermodynamic efficiency as well as friction [24] and increased wear in the contact pairs and bearing surfaces of an IC engine [1].…”
Section: Introductionmentioning
confidence: 73%
“…At the same time, ethanol has some tribological issues connected with engine oil dilution and corrosion [21] due to the inherent oxygen and moisture. Research [22] confirms that ethanol generally increases wear while having a minimal impact on the aging performance of lubricant oil [23]. Therefore, it could be concluded that conventional fuel modification by adding alternative fuels results in dilution and degradation of engine oil, which affect thermodynamic efficiency as well as friction [24] and increased wear in the contact pairs and bearing surfaces of an IC engine [1].…”
Section: Introductionmentioning
confidence: 73%
“…There have been long-standing concerns regarding the friction and wear performance implications on the piston ring pack as result of fuel dilution by high-ethanol-content fuels [13,14]. A recent review on the tribology of ethanol-fuelled engines highlights both rheological and additive chemistry ethanol lubricant interactions [15].…”
Section: Introductionmentioning
confidence: 99%
“…As the transition to electric vehicles will be slow and not occur at the same pace or proportions in all regions, low-carbon renewable fuels will still be needed for many years to come to eliminate fossil fuel use (which leads to a high carbon footprint) [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…to come to eliminate fossil fuel use (which leads to a high carbon footprint) [9][10][11]. In the search for sustainable energy sources, the synthesis of methane gas from urban solid residues emerges as a viable option.…”
Section: Introductionmentioning
confidence: 99%